Childhood vaccination as a protective factor for developmental psychopathology. (November 2020) - Kim, Bora; Ha, Mina; Kim, Young Shin; Koh, Yun-Joo; Kwon, Ho-Jang; Lim, Myung-Ho; Paik, Ki-Chung; Kim, Hosanna; Hong, Patricia; Leventhal, Bennett L.
Abstract: Backgrounds: Despite multiple studies demonstrating no relationship between childhood vaccination and increasing Autism Spectrum Disorder (ASD) prevalence, parental fear for vaccination and subsequent refusal to vaccinate their children continue, resulting in recent outbreaks of childhood infections such as measles in the US. We examine the relationship between the completion of 6 recommended vaccinations in childhood and the likelihood for having developmental psychopathology. Methods: Two large-scale South Korean epidemiologic samples were used to examine whether completion of childhood vaccinations decrease likelihood of having ASD as assessed by Autism Spectrum Screening Questionnaire (ASSQ) and behavioral problems scores. Parental reports on vaccination completion were categorized in groups: <3, 4−5, & 6. The primary outcome is the likelihood of having ASD and/or, internalizing, and externalizing behavioral symptoms. Likelihood of having ASD was categorized as: low (ASSQ < 10), intermediate (ASSQ = 10–14), and high (ASSQ ≥ 15). The risk for externalizing/internalizing symptoms was assessed with the Behavior Assessment System for Children-Parent Rating Scale. We examined the hypothesis in a Discovery Sample (DS) (N = 10, 006) and verified findings in a Replication Sample (RS) (N = 29, 381). Results: 84.3 % of DS and 80.1 % of RS participants were fully vaccinated. In the DS, after adjusting for demographics and confounders, children with incomplete-vaccinations were at greater risk for ASD when compared to those fully vaccinated (adjusted odds ratio [aOR] = 1.42, 95 % Confidence Interval [CI] 1.17−1.73 with 4−5 vaccinations; aOR = 2.33, CI 1.53−3.56 with vaccination <3). The DS finding was confirmed in the RS (aOR = 1.44, CI 1.32−1.58 with 4−5 vaccinations and aOR = 2.19, CI 1.80−2.67 with < 3 vaccinations). In the DS, those with incomplete-vaccinations were at a greater risk for internalizing and externalizing symptoms. Conclusions: We replicate our own and prior findings that vaccination does not increase ASD risk. Further, completing recommended vaccinations may offer protection against the risk of having ASD and other developmental psychopathology.